Enhancing the wear and corrosion resistance of TiZrHfTa refractory high-entropy alloys via additive manufacturing - Zairan Luo; Qian Liu; Jiang Yi; MuJin Yang; Zhiqian Rao; Shi Shi; Shuai Wang (Journal of Materials Research and Technology)
Refractory high-entropy alloys (RHEAs) represent a class of advanced metallic materials tailored for extreme environments due to their exceptional mechanical strength, thermal stability, and resistance to wear and corrosion. However, their high hardness and low atomic diffusivity pose challenges for conventional processing methods, constraining microstructural tailoring and property optimization. In this study, a novel powder-free laser powder bed fusion (PF-LB-PBF) method is introduced for the fabrication of TiZrHfTa RHEAs, enabling the formation of a laser-induced compositional and structural gradient. The rapid thermal cycling (cooling rates of 106–108 K/s) during the process promotes phase decomposition, yielding a triplex-phase microstructure composed of a BCC matrix, HCP precipitates, and eutectic regions. This microstructure leads to significant grain refinement, reducing the average grain size from 150 μm to 25 μm (>83 % reduction), while enhancing mechanical properties, with microhardness increasing from 360 HV to 659 HV (an 83 % improvement). Moreover, the laser-treated surface exhibits enhanced wear and corrosion resistance, with a 75 % reduction in wear rate (2.86 × 10−4 mm3/N·m) and corrosion current density decreased by an order of magnitude (6.82 × 10−8 A/cm2). These findings highlight the potential of the PF-LB-PBF approach in engineering oxide-free, property-optimized RHEA surfaces for high-temperature and corrosive applications.